From river blindness to river epilepsy: Implications for onchocerciasis elimination programmes - Colebunders,R; Siewe,Fodjo JN; Hopkins,A; Hotterbeekx,A; Lakwo,TL; Kalinga,A; Logora,MY; Basáñez,M-G (PLoS Neglected Tropical Diseases, 2019)
Current onchocerciasis elimination programmes do not include identification and management of onchocerciasis-associated epilepsy (OAE) in their strategies. Creating awareness about OAE will increase community-directed treatment with ivermectin (CDTI) adherence, particularly in areas of high prevalence, while motivating funders and stakeholders not to relent their efforts in the fight against onchocerciasis. Strengthening onchocerciasis elimination efforts should be prioritised wherever epilepsy prevalence is high in order to reduce OAE-related morbidity and mortality. In such areas, alternative treatment strategies including biannual CDTI, ground larviciding of blackfly breeding sites, and/or treatment with moxidectin should be considered. Addressing the OAE disease burden in these generally remote onchocerciasis-endemic regions confronted with poverty, weak healthcare infrastructures, and insecurity goes beyond current onchocerciasis elimination plans. New strategies with appropriate budgets are required. A morbidity management and disease prevention (MMDP) strategy, fully integrated into the health system, must be developed by multidisciplinary working groups involving neglected tropical disease (NTD) and epilepsy specialists, advocacy experts, and persons from affected communities. ‘River epilepsy’ needs to be urgently recognised and placed in the international development and NTD agendas.